Mental health, sleep, and pain in elite para athletes and the association with injury and illness—A prospective study - Fagher, K.; Dahlström, Ö.; Lexell, J. (PM&R, 2023)
Introduction The interest in the health of Para athletes continues to increase. Still, there are few studies that have evaluated health parameters beyond injury and illness in this athlete population.